Book profile: On bullshit - Lerner, Berel Dov (The journal for cultural and religious theory, 2005)
A profile of Harry G. Frankfurt, On Bullshit. Princeton, NJ: The Princeton University Press, 2005. 67 pp. $9.95 (cloth). ISBN: 0-6911-2294-6.